2017
DOI: 10.14814/phy2.13339
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity interval exercise and glycemic control in adolescents with type one diabetes mellitus: a case study

Abstract: Current physical activity guidelines for youth with type 1 diabetes (T1D) are poorly supported by empirical evidence and the optimal dose of physical activity to improve glycemic control is unknown. This case report documents the effect of acute high‐intensity interval exercise (HIIE) and moderate‐intensity exercise (MIE) on 24‐h glycemic control in three adolescents with T1D using continuous glucose monitoring. Results highlight varied individual response to exercise across the participants. In two participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This intermittent choice of activity may be based on enjoyment, as it has been previously shown in young people aged 12–15 that enjoyment ratings are higher for intermittent than for continuous cycling exercise, and that enjoyment remains high even when bouts of exercise are at near maximal intensity 44 , 45 . Giving young people the choice to stop and start and to speed up and slow down during The Daily Mile may also be important for physiological health and cognitive function benefits, as glycaemic control and executive function were better in adolescents following intermittent in comparison with continuous exercise 46 , 47 . Therefore, the findings of the present study support the use of The Daily Mile as an intermittent form of activity in young people.…”
Section: Discussionmentioning
confidence: 99%
“…This intermittent choice of activity may be based on enjoyment, as it has been previously shown in young people aged 12–15 that enjoyment ratings are higher for intermittent than for continuous cycling exercise, and that enjoyment remains high even when bouts of exercise are at near maximal intensity 44 , 45 . Giving young people the choice to stop and start and to speed up and slow down during The Daily Mile may also be important for physiological health and cognitive function benefits, as glycaemic control and executive function were better in adolescents following intermittent in comparison with continuous exercise 46 , 47 . Therefore, the findings of the present study support the use of The Daily Mile as an intermittent form of activity in young people.…”
Section: Discussionmentioning
confidence: 99%
“…Herzig et al [40] showed that high-risk participants who engaged in 3 months of light-intensity walking exercise (equivalent to ≈3 km h −1 ) had significantly decreased fasting glucose, HOMA-IR, total cholesterol, and visceral fat. Conversely, Cockcroft et al debated that a single bout of high-intensity activity was more beneficial in improving glucose tolerance compared to a moderate-intensity workout when measured immediately after exercise [41]. Despite these conflicting results, the majority of the research studies are in agreement that the total duration of PA appears to be more important for insulin response than the level of the workout intensity [40,[42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“… 20 Recent evidence suggests the positive impact of acute exercise on systemic inflammatory mediators on immune cells regardless of weight or fat loss. 21 In a study by Cockcroft et al, 22 in a 24-hour period, the average blood glucose level was lower for all participants in the acute exercise condition. The novelty of the present study is the effect of a single exercise session with the standard protocol of the American Association (50%–70% of the maximum heart rate) 23 on blood glucose, which has scarcely been studied earlier.…”
Section: Introductionmentioning
confidence: 89%